Production and Characterization of Antimicrobial Electrospun Nanofibers Containing Polyurethane, Zirconium Oxide and Zeolite - OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN (SPRINGER, 2018)
In this study, electrospinning technique has been utilized to prepare composite nanofiber mats of polyurethane (PU)/zirconium dioxide (ZrO2) and PU/zeolite, consisted by antimicrobial properties. Tensile strength measurement test was performed for the mechanical analysis of the nanofibers. Scanning electron microscopy (SEM) were performed for displaying the morphological features of the fiber structure. XRD tests were performed for revealing the chemical structure. Antimicrobial tests were also performed to display antimicrobial effects of the produced materials. In vitro test was also performed to determine cytotoxicity and biocompatibility. The present PU/ZrO2 and PU/zeolite composite nanofibers resulted with improved mechanical properties and good antimicrobial properties against either their pure forms or other studies. Cell proliferation and viability also increased significantly with increase in zeolite and ZrO2 ratio. It is concluded that this composition provides a novel alternative as an antimicrobial material which can be suitable as a wound dressing or a coating material for various healthcare engineering applications.
Keywords: Polyurethane; Zirconia; Zeolite; Electrospinning; Nanofibers; Antimicrobial activity; FIBERS; ANTIBACTERIAL; NANOPARTICLES; FABRICATION; SILVER